Evil as Privation in Neoplatonism. Simplicius and Philoponus in Defense of Matter - Cardullo, R. Loredana (Peitho. Examina Antiqua, 2017)
The aim of this paper is to highlight the decisive contribution of Simplicius and Philoponus to the resolution of the problem of evil in Neoplatonism. A correct and faithful interpretation of the problem, which also had to agree with Plato’s texts, became particularly needed after Plotinus had identified evil with matter, threatening, thus, the dualistic position, which was absent in Plato. The first rectification was made by Proclus with the notion of parhypostasis, i.e., “parasitic” or “collateral” existence, which de-hypostasized evil, while at the same time challenging the Plotinian theory that turned evil into a principle that was ontologically opposed to good. In light of this, the last Neoplatonic exegetes, Simplicius and Philoponus, definitely clarified the “privative” role of kakon, finally relieving matter from the negative meaning given to it by Plotinus and restoring metaphysical monism.